Analisis Kualitas Layanan Data Pokok Pendidik (Dapodik) Pada Smk Negeri 1 Palembang Menggunakan Metode Webqual 4.0 - Sari, Nova Vuspita; Kesuma, Hendra Di; Kholik, Abdul (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
The object of this research is the educator basic data information system (DAPODIK at SMK Negeri 1 Palembang. this research aims to test the quality of information system services. the sample used in this research was school teachers as system users. the sampling technique uses non-probability sampling. the number of samples in this study was 70 respondents. this research uses a qualitative approach. the data analysis technique used for hypothesis testing is path analysis. The method used in this research is Webqual 4.0, which uses 4 indicators: usability, information quality, service interaction quality, and user satisfaction. based on Webqual 4.0 variables. the results of the analysis show that the usability quality score is 2,800 with a percentage level of 84.25%, supported by regression, which proves usability quality has a significant positive effect on user satisfaction. the information quality score result is 2,450 with a percentage level of 84.45%, supported by regression, which proves that information quality has a significant positive effect on user satisfaction, while the service quality score result is 2,100 with a percentage level of 81.33%, supported by regression which proves service quality has a positive effect significant to user satisfaction.